Your time is now get what God has given you - Evans, Jonathan 1981- (Minneapolis, Minnesota Bethany House, a division of Baker Publishing Group, 2021)
Now -- But -- Look -- Go -- Dress -- For -- Wait -- Yes -- Now.
"God has a purpose for you right now. As you read about the Old Testament leader Joshua as a model for stepping up to God's big calling, you will be inspired to discover how God wants to use you in His kingdom. If you will be steadfast and always abound in God's calling, you'll see that it will not be in vain. God wants to do great things through you!"--
Keywords: Joshua -- (Biblical figure); Christian Life; Self-actualization (Psychology) -- Religious aspects -- Christianity